2014
DOI: 10.1001/jamaophthalmol.2014.93
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Doxycycline vs Placebo on Retinal Function and Diabetic Retinopathy Progression in Patients With Severe Nonproliferative or Non–High-Risk Proliferative Diabetic Retinopathy

Abstract: may contribute to the pathogenesis of diabetic retinopathy (DR). OBJECTIVES To investigate, in a proof-of-concept clinical trial, whether low-dose oral doxycycline monohydrate can (1) slow the deterioration of, or improve, retinal function or (2) induce regression or slow the progression of DR in patients with severe nonproliferative DR (NPDR) or non-high-risk proliferative (PDR), and to determine the potential usefulness of visual function end points to expedite the feasibility of conducting proof-of-concept … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 46 publications
(14 reference statements)
2
41
2
1
Order By: Relevance
“…Indeed, Scott et al 30 recently used FDP as a clinical trial end point to evaluate the efficacy of doxycycline in preserving retinal sensitivity during diabetes. They found that doxycycline treatment was associated with improved FDP sensitivity at the end of the 24-month trial, although further work is needed to understand the clinical significance of improvements in FDP sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Scott et al 30 recently used FDP as a clinical trial end point to evaluate the efficacy of doxycycline in preserving retinal sensitivity during diabetes. They found that doxycycline treatment was associated with improved FDP sensitivity at the end of the 24-month trial, although further work is needed to understand the clinical significance of improvements in FDP sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The 2-year results showed that foveal sensitivity (measured by photopic visual field) decreased among the placebo group, while it increased in the group receiving doxycycline, when compared with baseline. However, all other anatomical and functional outcomes were not significantly different between the two groups [94].…”
Section: Proliferative Diabetic Retinopathy (Pdr) and Nonproliferativmentioning
confidence: 74%
“…In a pilot proofof-concept study (single-center, prospective, and open-label phase I/II clinical trial) with patients with diabetic macular edema, the treatment with minocycline improved visual function, central macular edema, and vascular leakage [224]. In a randomized, double-masked clinical trial in patients with severe nonproliferative diabetic retinopathy or nonhigh-risk proliferative diabetic retinopathy, doxycycline, a semisynthetic second-generation tetracycline also with antiinflammatory properties, improved foveal frequency doubling perimetry, suggesting a link between a low-dose of this oral anti-inflammatory agent and subclinical improvement in inner retinal function [225].…”
Section: Diabetic Retinopathymentioning
confidence: 99%